Mini Tinjauan Literatur : Pemanfaatan Software Math Master untuk Berpikir Komputasi Siswa - Ekki Wahyuni Lubis; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study is a mini literature review aimed at exploring the use of the Math Master software in enhancing students’ computational thinking skills. Computational thinking is a crucial 21st-century skill, particularly in technology-based mathematics learning. This article reviews several relevant studies that discuss the use of educational software, specifically Math Master, in helping students solve mathematical problems systematically, logically, and efficiently. The review findings indicate that Math Master can serve as an interactive tool that supports conceptual understanding and encourages algorithmic thinking among students.